Pengembangan Media Kartu Domino Pancasila untuk Meningkatkan Kemampuan Berpikir Kritis Mata Pelajaran Pendidikan Pancasila SD - Suci Anis Kunaifi; Ari Wibowo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aimed to assess the level of validity, practicality, and effectiveness of Pancasila domino card media in fostering students’ critical thinking skills. The research utilized a Research and Development (R&D) design adapted from the Borg and Gall model to suit the study requirements. Data collection was conducted using interviews, observations, questionnaires, and achievement tests. The instruments consisted of validation sheets completed by experts to validity, questionnaires distributed to determine practicality, and pretest–posttest instruments to effectiveness. The subjects of this research were 23 fourth-grade students NU Galur Elementary School, along with 5 students Trayu Elementary School involved in a limited trial phase. The results indicated that the developed media successfully met the criteria of being valid, practical, and effective. The validation results showed percentages of 88% from media experts and 96% from material experts, both categorized as very valid. Meanwhile, practicality was demonstrated through positive responses from teachers (95.5%) and students (92.46%), which fell into the very practical category. Furthermore, the effectiveness of the media was reflected in the substantial increase in students’ learning outcomes, with the average score rising from 43.73 in the pretest to 86.66 in the posttest. Statistical analysis using a paired sample t-test revealed a significance value below 0.001 (<0.05), indicating a meaningful difference between the two tests. In addition, the N-Gain score of 0.76 was classified as high. These findings suggest that the Pancasila domino card media is capable of effectively enhancing students’ critical thinking abilities.